2010
DOI: 10.1016/j.pocean.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of likely foraging habitat of pelagic loggerhead sea turtles (Caretta caretta) in the North Atlantic through analysis of telemetry track sinuosity

Abstract: Changes in the behavior of individual animals in response to environmental characteristics can provide important information about habitat preference, as well as the relative risk that animals may face based on the amount of time spent in hazardous areas. We analyzed movement and habitat affinities of ten loggerhead turtles (Caretta caretta) tagged with satellite transmitters in the spring and fall of 1998 near Madeira, Portugal for periods of 2-10 months. We analyzed the behavior of these individuals in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Changes in path straightness have been used to identify purported search behavior associated with foraging in leatherbacks [25], as well as other marine predators [67][69]. Density plots of the environmental data showed that logarithmic transformation was required for SST gradient, chl a , chl a gradient and bathymetry.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in path straightness have been used to identify purported search behavior associated with foraging in leatherbacks [25], as well as other marine predators [67][69]. Density plots of the environmental data showed that logarithmic transformation was required for SST gradient, chl a , chl a gradient and bathymetry.…”
Section: Methodsmentioning
confidence: 99%
“…Sufficient empirical evidence for confident conclusions about surface-pelagic distribution and ecology as juveniles is available for only 1 species, the loggerhead sea turtle Caretta caretta. Loggerhead juveniles have been directly sampled in situ, including captures of post-hatchlings off nesting beaches (Witherington 2002) and captures of large juveniles (mostly 150 to 550 mm straight carapace length, SCL) foraging in the open sea (Carr 1986, Bolten 2003b, McCarthy et al 2010. These studies have provided empirical information on behavior, habitat associations, and diet specific to an occupied habitat.…”
Section: Sea Turtles' Lost Year(s)mentioning
confidence: 99%
“…These studies have provided empirical information on behavior, habitat associations, and diet specific to an occupied habitat. For the largest surface-pelagic juvenile loggerheads (500 to 700 mm SCL), researchers have used satellite telemetry and remote sensing to identify coarse features of habitat traversed by turtles in the Central Pacific , Howell et al 2008 and in the eastern North Atlantic (Bolten 2003b, McCarthy et al 2010.…”
Section: Sea Turtles' Lost Year(s)mentioning
confidence: 99%
“…3A,B); the 60 day mean sea surface temperatures experienced by virtual turtles was suitable for loggerheads (>14°C) in all simulations. Additionally, evidence exists that juvenile loggerheads near the islands of the Azores and Madeira spend extended periods in the Canary Current System and even make seasonal migrations north and south within it (McCarthy et al, 2010). The eastern Atlantic is highly productive , suggesting that it is a favorable foraging area for young, pelagic loggerheads.…”
Section: Non-oriented Swimming Responsesmentioning
confidence: 99%